Renegotiating the city: Refugee resettlement between surveillance, austerity, and activism in German urban communities - Miao-ling Hasenkamp (Globalizations, 2024)
This paper investigates the politics of refugee arrival and integration at urban level in Germany following the migration influx in summer 2015. How have cities redefined themselves? How have newcomers and residents with different subjectivities constructed their identity, social belonging, and justified their rights-claiming? What kind of changes can be observed in city's social spaces? Supported by critical geography, securitization, ethnographic approaches, the paper aims to identify the grey areas of the urban social spaces and presents two accounts centred on: (1) city as sites of bureaucratic politics, austerity urbanism and surveillance; (2) city as sites of sanctuary/solidarity practices. It argues that the refugees' arrival offers the chance for German cities to envision a social project through engaging a politics of `bounding' which involves the re-framing of refugee displacement in relation to urban development by covering both the lived (camp) experiences of those on the move and local population's needs.
Keywords: 320; moral urbanism; refugee resettlement and integration in Germany; austerity urbanism; surveillance measures and crimigation; identity- and boundary-making in German cities